A systemic study on key parameters affecting nanocomposite coatings on magnesium substrates. (May 2016) - Johnson, Ian; Wang, Sebo Michelle; Silken, Christine; Liu, Huinan
Graphical abstract: Abstract: Nanocomposite coatings offer multiple functions simultaneously to improve the interfacial properties of magnesium (Mg) alloys for skeletal implant applications, e.g., controlling the degradation rate of Mg substrates, improving bone cell functions, and providing drug delivery capability. However, the effective service time of nanocomposite coatings may be limited due to their early delamination from the Mg-based substrates. Therefore, the objective of this study was to address the delamination issue of nanocomposite coatings, improve the coating properties for reducing the degradation of Mg-based substrates, and thus improve their cytocompatibility with bone marrow derived mesenchymal stem cells (BMSCs). The surface conditions of the substrates, polymer component type of the nanocomposite coatings, and post-deposition processing are the key parameters that contribute to the efficacy of the nanocomposite coatings in regulating substrate degradation and bone cell responses. Specifically, the effects of metallic surface versus alkaline heat-treated hydroxide surface of the substrates on coating quality were investigated. For the nanocomposite coatings, nanophase hydroxyapatite (nHA) was dispersed in three types of biodegradable polymers, i.e., poly(lactic-co-glycolic acid) (PLGA), poly(l -lactic acid) (PLLA), or poly(caprolactone) (PCL) to determine which polymer component could provide integrated properties for slowest Mg degradation. The nanocomposite coatings with or without post-deposition processing, i.e., melting, annealing, were compared to determine which processing route improved the properties of the nanocomposite coatings most significantly. The results showed that optimizing the coating processes addressed the delamination issue. The melted then annealed nHA/PCL coating on the metallic Mg substrates showed the slowest degradation and the best coating adhesion, among all the combinations of conditions studied; and, it improved the adhesion density of BMSCs. This study elucidated the key parameters for optimizing nanocomposite coatings on Mg-based substrates for skeletal implant applications, and provided rational design guidelines for the nanocomposite coatings on Mg alloys for potential clinical translation of biodegradable Mg-based implants. Statement of Significance: This manuscript describes the systemic optimization of nanocomposite coatings to control the degradation and bioactivity of magnesium for skeletal implant applications. The key parameters influencing the integrity and functions of the nanocomposite coatings on magnesium were identified, guidelines for the optimization of the coatings were established, and the benefits of coating optimization were demonstrated through reduced magnesium degradation and increased bone marrow derived mesenchymal stem cell (BMSC) adhesion in vitro . The guidelines developed in this manuscript are valuable for the biometal field to improve the design of bioresorbable implants and devices, which will advance the clinical translation of magnesium-based implants.